Analyzing User Acceptance Factors in Digital E-Ticketing Systems Using Extended UTAUT2 Framework - Achmad Rafi Argya Rasya; Anita Wulansari; Eristya Maya Safitri (Komunitas Dosen Indonesia, 2025)
Digital ticketing platforms are reshaping fan engagement in Indonesia’s football ecosystem. This study examines acceptance of PSSI’s Kita Garuda platform by testing how instrumental benefits (usefulness and ease), social cues, enjoyment, price value, and enabling conditions relate to users’ intention to keep using the service. We extend UTAUT2 with two well-motivated additions: Service Satisfaction, which captures whether the end-to-end experience meets expectations, and Psychological Discomfort, which indexes anxiety or unease when transacting online. Using survey data and Partial Least Squares Structural Equation Modeling with bootstrapping, we find that Performance Expectancy (t=4.58, p<0.001), Effort Expectancy (t=3.92, p<0.001), Hedonic Motivation (t=5.03, p<0.001), Price Value (t=4.20, p<0.001), and Social Influence (t=3.12, p=0.002) significantly predict continued intention, whereas Facilitating Conditions (t=1.45, p=0.144) and Habit (t=1.60, p=0.110) do not. Measurement quality met conventional thresholds (α≥0.85; CR>0.90; AVE>0.50). Service Satisfaction helps explain why benefits translate into ongoing use higher satisfaction strengthens the link between perceived benefits and intention (partial mediation). Psychological Discomfort weakens the positive association between intrinsic drivers especially enjoyment and intention (interaction significant, p<0.05). Results are robust to alternative specifications and item-deletion diagnostics; bootstrapped confidence intervals exclude zero across significant paths. Practical implications are clear: reduce sources of anxiety (transparent pricing, reliable payment and QR validation, responsive helpdesk), and invest in a seamless, enjoyable flow to elevate satisfaction and loyalty. By reporting effect magnitudes and significance, this study offers transparent account of drivers continued use for sports ticketing in an emerging market context and points to actionable levers for platform design and fan experience.